2020
DOI: 10.3892/etm.2020.8678
|View full text |Cite
|
Sign up to set email alerts
|

Men with idiopathic oligoasthenoteratozoospermia exhibit lower serum and seminal plasma melatonin levels: Comparative effect of night‑light exposure with fertile males

Abstract: Melatonin is a darkness hormone secreted by the pineal gland, which serves a role in idiopathic oligoasthenoteratozoospermia (iOAT). The present study aimed to evaluate the seminal plasma and serum melatonin levels of 50 patients with iOAT and 50 normal fertile controls and the effects of exposure to light at night on semen parameters. Semen analyses were performed according to the World Health Organization 2010 guidelines. Measurements of serum and seminal plasma melatonin, serum TSH, FT3, FT4, free testoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(31 reference statements)
2
7
0
2
Order By: Relevance
“…Melatonin is a hormone by N-acetyl-5-methoxy chemical formula, which is produced in the pineal gland in the brain while helps regulate the sleep-wake cycle in the body (Pereira et al, 2020). The secretion level of this hormone reaches a maximum at night and decreases around noon (Hassan et al, 2020;Pereira et al, 2020). Melatonin is synthesised from the essential amino acid tryptophan to serotonin and also a low level of melatonin (Pereira et al, 2020).…”
mentioning
confidence: 99%
“…Melatonin is a hormone by N-acetyl-5-methoxy chemical formula, which is produced in the pineal gland in the brain while helps regulate the sleep-wake cycle in the body (Pereira et al, 2020). The secretion level of this hormone reaches a maximum at night and decreases around noon (Hassan et al, 2020;Pereira et al, 2020). Melatonin is synthesised from the essential amino acid tryptophan to serotonin and also a low level of melatonin (Pereira et al, 2020).…”
mentioning
confidence: 99%
“…Fertile men have higher melatonin seminal [ 223 , 224 ] and serum levels [ 224 ] than infertile men. This hormone has proven to decrease DNA fragmentation and MDA, and increase sperm viability [ 221 ].…”
Section: Antioxidantsmentioning
confidence: 99%
“…Melatonin was shown as well to protect spermatogonia stem cells in-vitro [ 222 ]. The disruption of the sleep-wake cycle and its relationship with spermatic parameters was also studied; in a 2020 case-control study men with nigh-shifts or light exposure during the night, showed diminished sperm concentration and motility as well as an increase of abnormal spermatozoa forms [ 224 ]. A systematic review and meta-analysis about melatonin and ART concluded melatonin enriched cultures yield higher quality embryos [ 225 ]; another interesting experimental study measured microRNAs (miRNAs) in the follicular ambient based on the melatonin profile of female patients, finding miRNAs to be a good non-invasive marker of good quality embryos and melatonin supplementation to yield higher quality oocytes [ 226 ].…”
Section: Antioxidantsmentioning
confidence: 99%
“…Дежурное ночное освещение в животноводческих помещениях нарушает циркадные ритмы. Показано, что синяя составляющая спектра, в том числе искусственного освещения, в значительной степени подавляет продукцию гормона мелатонина, от секреции которого зависит качество сна животных (128). В свою очередь, мелатонин опосредовано оказывает регулирующее влияние на функции тестикул (129,130).…”
Section: содержание эндогенных гормонов в сыворотке крови у голштинских быковunclassified